2019
DOI: 10.1182/blood.2019000840
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and incident cardiovascular events following ibrutinib initiation

Abstract: In a retrospective analysis, Dickerson et al report that the incidence of hypertension in patients treated with ibruitinib is nearly 80% and is associated with an increased rate of adverse cardiovascular events, primarily atrial fibrillation. Cardiac events can be reduced by treating the hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
171
3
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(188 citation statements)
references
References 44 publications
(66 reference statements)
6
171
3
8
Order By: Relevance
“…Nevertheless, this would only be true for milder AEs, as the more severe AEs were always reported. We identified 6.8% patients with any grade hypertension, which is remarkably lower than previously reported; a recent study reported 71.6% patients developing de novo hypertension during ibrutinib treatment, 20 whereas in the RESONATE and RESONATE‐2 studies 21%‐26% reported hypertension 15,21 . The difference probably reflects the retrospective nature of this study and that hypertension primarily is managed in general practice, thus not fully documented in hospital records.…”
Section: Discussioncontrasting
confidence: 65%
“…Nevertheless, this would only be true for milder AEs, as the more severe AEs were always reported. We identified 6.8% patients with any grade hypertension, which is remarkably lower than previously reported; a recent study reported 71.6% patients developing de novo hypertension during ibrutinib treatment, 20 whereas in the RESONATE and RESONATE‐2 studies 21%‐26% reported hypertension 15,21 . The difference probably reflects the retrospective nature of this study and that hypertension primarily is managed in general practice, thus not fully documented in hospital records.…”
Section: Discussioncontrasting
confidence: 65%
“…Ibrutinib, an irreversible inhibitor of Bruton’s tyrosine kinase, is indicated in advanced B-cell malignancy. It is implicated in new onset hypertension in 49% and CTCAE grade 3 hypertension in 16% [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Hypertensive Cardiotoxicities Of Cancer Therapiesmentioning
confidence: 99%
“…1,2 A recent retrospective analysis of 562 patients receiving ibrutinib at the Ohio State University also noted a marked incidence of new hypertension of 72%. 7 Major cardiac events were noted in 17% of patients and occurred more frequently in those with new or worsening hypertension (19%). In a separate aggregated data set of over 1000 patients receiving ibrutinib, 10 events of sudden death or cardiac arrest were identified.…”
Section: Resultsmentioning
confidence: 99%